சங்க இலக்கியத்தில் வாழ்வியல் அறம்: The virtue of life in Sangam literature - M, Geetha (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2025)
The history and culture of the Tamils during the Sangam period were outstanding. The history of a country, the lifestyle of the people and the relationship between the king and the people can be known through literature. The set of moral systems that a person has defined for himself is called virtue. Virtuous qualities enrich human life. In that way, literature that expresses the concepts of virtue has been appearing in Tamil from time to time. The research article titled 'Virtue of Life in Sangam Literature' has been examined under the sub-topics of introduction, virtue - definition of meaning, virtue of life, homeliness, hospitality, education system, charity, and virtue of merchants. A conclusion is given at the end of the article. சங்க காலத்தில் தமிழர்களின் வரலாறும், பண்பாடும் தலைசிறந்து விளங்கின. ஒரு நாட்டின் வரலாறும், மக்களின் வாழ்க்கை முறைகளும் அரசனுக்கும் மக்களுக்கும் உள்ள தொடர்பும் இலக்கியங்கள் வாயிலாக தெரிந்து கொள்ள முடிகின்றது. மனிதன் தனக்கென வரையறுத்துக் கொண்ட ஒழுக்க முறைகளின் தொகுதியே அறம் எனப்படும். மனித வாழ்வை செழுமையாக்குபவை அறப் பண்புகள். அந்த வகையில் காலந்தோறும் தமிழில் அறக்கருத்துக்களைக் கூறும் இலக்கியங்கள் தோன்றிய வண்ணம் இருக்கின்றன. 'சங்க இலக்கியத்தில் வாழ்வியல் அறம்' என்னும் தலைப்பிலான ஆய்வுக் கட்டுரையில் முன்னுரை, அறம் - சொற்பொருள் விளக்கம், வாழ்வியல் அறம், இல்லறம், விருந்தோம்பல் பண்பு, கல்வி முறை, ஈகைச் சிறப்பு, வணிகர்களின் அறம் ஆகிய துணைத் தலைப்புகளில் ஆராயப்பட்டுள்ளது. கட்டுரையின் நிறைவில் முடிவுரை வழங்கப்பட்டுள்ளது.